Common Fixed Point Theorems for Mappings of Compatible Type(A) in Dislocated Metric Space - Panthi, Dinesh; Kumari, P. Sumati (Nepal Journal of Science and Technology, 2016)
In this article we establish a common fixed point result for two pairs of mappings of compatible type(A) in dislocated metric space which generalizes and extends the similar results in the literature. Nepal Journal of Science and Technology Vol. 16, No.1 (2015) pp. 79-86